Effect of Breathing Nostril and Back Massage On Blood Pressure Reduction in Hypertension Patients in The Working Area of Hospital Pertamina Jaya - Sofyan Sofyan; Rohman Azzam; Mustikasari Mustikasari (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Hypertension is an abnormal increase in blood pressure in the arteries continuously for more than one period. Handling of hypertension can be done with secondary prevention such as nostril breathing and back massage techniques. This study aims to determine the effect of nostril breathing and back massage on lowering blood pressure in hypertension in the working area of Pertamina Jaya Hospital. The research design used was a quantitative research design with the research method Quasy Experiment pretest and posttest with the control group. The total sample was 76 respondents who experienced hypertension. The nostril breathing and back massage intervention group consisted of 38 respondents and the control group 38. Blood pressure was measured using a tool. The statistical test used is the dependent t-test and the results obtained are systolic 0.000 and p-value diastolic 0.000. Based on the results of the analysis, this non-pharmacological therapy affects reducing blood pressure.